A Cascading Failures Perspective Based Mesoscopic Reliability Model of Weighted Public Transit Network considering Congestion Effect and User Equilibrium Evacuation. (10th May 2018) - Zhang, Lin; Lu, Jian; Long, Man; Li, Shu-bin; Zhou, Jialin
Abstract : To establish the optimal route layout estimation technology based on reliability optimization, a more accurate and realistic reliability model of a weighted public transit network (PTN) is the indispensable basis. This paper establishes a cascading failures (CFs) perspective based mesoscopic reliability model for measuring PTN survivability. First, a modeling method for abstracting weighted PTN and determining its initial passenger flow and bearing capacity is proposed, making the network passenger flow pattern follow the aggregated flow pattern. Second, three basic concepts (time step, congestion effect of a road section, and CFs judging method) for establishing the CFs model are defined to clarify the overall evolution process of CFs. Furthermore, the aggregated passenger flow evacuation that exists in an emergency occurring at a station (i.e., failure load dynamic redistribution (FLDR)) is considered as a conscious dynamic game process through following the user equilibrium rule. As a result, a novel CFs model that considers congestion effect and user equilibrium evacuation is obtained. Finally, based on the collected data of Jinan's PTN, a case simulation analysis is conducted to verify the adaptability of this model through showing a significantly different dynamics characteristic with the existing FLDR patterns and to provide optimization direction for effectively controlling PTN survivability, that is, guide the transformation among varying FLDR patterns through some technical measures or traffic policies.